Determinación de los coeficientes de digestibilidad ileal aparente y estandarizada de la proteína y aminoácidos de la torta de canola en lechones recién destetados - Mariscal, Gerardo; Reis, Tércia C.; Parra, Jaime E. (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary To obtain the coefficients of apparent ileal digestibility (CAID) and standardized ileal digestibility (CSID) of protein and amino acid from canola, one experiment was carried out using 24 piglets weaned at 17 days of age, weighing 5.5 kg. Piglets were fitted with a simple "T" cannula at terminal ileum and were fed with one of three treatments: (RD) reference diet elaborated with casein as unique protein source and corn starch; casein-canola meal (CCM) and casein-peletized canola meal (CPCM) diets. In those diets 10% CM or PCM was included. CAID were higher (p < 0.05) in RD than in CPCM diet and these than in CCM. CSID were ranked in the same way, PCM had higher CSID than CM. It was concluded that PCM can be useful at maximum level inclusion of 10% in weaned piglet food, because the peletized food significantly improve ileal digestibility of protein and amino acids.